Synthesis of graphene flakes over recovered copper etched in ammonium persulfate solution - M.K. Nizam,; D. Sebastian,; M.I. Kairi,; M. Khavarian,; A.R. Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The synthesis of high quality graphene via economic way is highly desirable for practical applications. In this study, graphene flake was successfully synthesized on Cu/MgO catalyst derived from recovered Cu via etching in ammonium persulfate solution. Recovered Cu acted as efficient active metal in Cu/MgO catalyst with good crystal structure and composition according to XRD and XRF results. FESEM, EDX, HRTEM, Raman spectroscopy and SAED analysis were carried out on the synthesized graphene. The formation of single, bilayer and few layer of graphene from Cu/MgO catalyst derived from recovered Cu was feasible.